Mussel-inspired near-infrared light-responsive gelatin-based hydrogels for enhancing MRSA-infected wound healing - Yang, Jian; Yu, Haojie; Wang, Li; Liu, Xiaowei; Huang, Yudi; Hong, Yichuan; Ren, Shuning (International journal of biological macromolecules, 2024)
Infected wound management is a great challenge to healthcare, especially in emergencies such as accidents or battlefields. Hydrogels as wound dressings can replace or supplement traditional wound treatment strategies, such as bandages or sutures. It is significant to develop novel hydrogel-based wound dressings with simple operation, inexpensive, easy debridement, effective antibacterial, biocompatibility, etc. Here, we designed a novel gelatin-based hydrogel wound dressing Gel-TA-Fe3+. The hydrogels used tannic-modified gelatin as the main body and Fe3+ as the crosslinking agent to achieve a controllable rapid sol-gel transition. The hydrogels exhibited tough mechanical properties, excellent antibacterial ability, biocompatibility and an acceptable temperature response to near-infrared light (NIR). Moreover, the hydrogels could promote the healing process of MRSA-infected skin wound in rats. This multifunctional hydrogel was thought to have potential for emergency treatment of bacterial infected wound.